Gallstone ileus and fatal gallstone coleus: the importance of the second stone. (15th March 2013) - Vaughan-Shaw, Peter G; Talwar, Anjay
Abstract : A patient was admitted as an emergency with bowel obstruction. Recent medical history included an episode of gallstone ileus treated surgically by removal of an enteric calculus. On this admission, an obstructing calculus was removed from the descending colon (gallstone coleus) at laparotomy. However, the postoperative course was complicated by sepsis and the patient died. A CT scan on the second admission and cytology results from a liver abscess suggested gallbladder malignancy as the underlying cause of the cholecystoenteric fistula. The technical challenge and increased mortality associated with cholecystoenteric fistula repair supports simple enterolithotomy as the preferred management of gallstone ileus. However, this case supports the need for a systematic search for all enteric stones at laparotomy and consideration of concurrent or interval cholecystectomy and cholecystoenteric fistula repair to prevent recurrent gallstone ileus and determine underlying pathology.